Come find me - Miranda, Megan (Crown, 2019)
"Told in two voices, sixteen-year-old Kennedy Jones and seventeen-year-old Nolan Chandler are drawn together by strange signals related to family tragedies, and find they are more connected than they could have imagined"--(Source of summary not specified)